Religious Symbolism and Democracy Encountered: A Case of Prostitution Bylaw of Bantul - Muhammad Latif Fauzi (Al-Jami'ah Research Centre, 2012)
This paper addresses the bylaw on prostitution issued by the Bantul authority in May 2007. It specifically examines the relation between the involvement of religious symbolism, the call for public participation and political interests in the legislation process. The paper argues that, on the one hand, the law relates prostitution to issues of immorality, social illness, and the degradation of women due to economic discrimination or sexual exploitation. The subject of prostitution has been extended, covering not only sex workers and pimps, but everyone committing indecent acts, such as showing a ‘sexy’ performance. On the other hand, this regulation is considered to be ambiguous in determining the standard of public morality and, therefore, puts women in a marginalised position. That the implementation of this law contributes to institutionalising the criminalisation against women is another fact which is believed to diminish the meaning of democracy. The government is blamed as taking too much care with procedural democracy but giving less attention to education and employment opportunities.[Artikel merupakan hasil studi peraturan daerah tentang larangan pelacuran yang dikeluarkan oleh Pemerintah Kabupaten Bantul pada Mei 2007. Studi ini menguji keterkaitan antara simbol-simbol keagamaan, partisipasi publik, dan kepentingan politik yang muncul dan menyertai proses legislasi. Penulis berpendapat bahwa pada satu sisi, dalam peraturan tersebut, pelacuran dikaitkan dengan perusakan terhadap nilai agama dan sosial serta penurunan martabat perempuan, terlepas akibat diskriminasi ekonomi atau eksploitasi seksual. Subjek pelacuran ternyata juga diperluas, tidak hanya pekerja seks dan mucikari, tetapi setiap orang yang melakukan perbuatan cabul, seperti berpenampilan seksi. Pada sisi yang lain, ukuran moralitas publik dalam peraturan ini dianggap kurang jelas dan menempatkan perempuan pada posisi yang terpinggirkan. Bahwa penerapan peraturan berimplikasi pada kriminalisasi terhadap perempuan merupakan bukti lain yang dinilai bertentangan dengan substansi demokrasi. Pemerintah dinilai terlalu perhatian pada demokrasi prosedural, tetapi mengabaikan masalah pendidikan dan kesempatan kerja.]